OVERVIEW OF OCCUPATIONAL HEALTH AND SAFETY IN TRANSPORTATION ACTIVITIES PT ANTAM (PT MEG CONTRACTOR PT ANTAM) - Manurung, Amos Parulian; Meilasari, Fitriana; Azwa, Nirmala; Sutrisno, Hendri; Soeryamassoeka, Stefanus Barlian (Fakultas Teknik Universitas Tanjungpura, 2022)
Occupational safety and health aim to create a safe and comfortable environment in carrying out activities or work. In PT ANTAM's bauxite transportation activities, there are still occupational safety and health risks. The purpose of this study was to determine the frequency rate, accident severity (Severity Rate), and Safe T Score in PT ANTAM's bauxite transportation activities. The research method used is a descriptive method, which is a research method that describes quantitative data according to the conditions in the field of bauxite transportation activities. The results of the study are (1) The results of the calculation of the frequency rate of 0 which indicate that there were no mining accidents in bauxite transportation activities in January-September 2019; (2) The result of the calculation of the severity rate (Severity Rate) of the accident is 0 which indicates the absence of the severity of the mining accidents that resulted in that month due to the absence of mining accidents that occurred in that month; (3) The results of the calculation of the safe T-score of 0 indicate the work accident control program does not show a significant change.